An analytical survey on implementing best practices for introducing e-learning programs to students - Mohammed, Husam Jasim; Mat Kasim, Maznah; AL-Dahneem, Ebtehal A.; Hamadi, Abdulmunaam K. (2016)
Today, a need has risen to reduce paper both to become “green” and to save costs.Shifting to an online course, to expand, the number of students who are participating in online courses and programs with significant global reach continues to increase dramatically.However, many studies showed that the failed retention rates for students of online institutions are bit higher than traditional classroom environments. This calls for analysing the current practices in the use of contents in online courses to improve e-learning student persistence.This is a conceptual paper sharing the specific best practice examples, observations, and outcomes from some leading universities, based on surveys of existing methodologies and practical experience. Special emphasis placed on current and future trends in effective online pedagogy. This paper identifies the best practices for introducing the students to e-learning experience in an analytical manner.The paper also analyses the various attributes of best practices in Elearning using Fuzzy AHP method of a Multi-Criteria Decision-Making (MCDM) method.The Fuzzy AHP involves several steps which include the setting of evaluation criteria and their weights, and evaluation of the E-learning technique as compared to the traditional learning technique for identifying the effect on response rates for different aspects of quality and time in order to explore the real worth in the use of e-learning. This paper shows that all the attributes behave comparable very well in the case of E-learning as compared to the traditional method.The analysis of our criteria which are essential for any effective learning demonstrated that the E-learning methods have good potential to grow.